EFEKTIVITAS PEMBERIAN SUKU BUNGA RENDAH TERHADAP PENINGKATAN PENJUALAN DI PT HOME CREDIT INDONESIA DISTRIC BANDUNG TIMUR - Egi, Egi Septian (JEBS (Journal of Economic and Business Student), 2023)
This study aims to determine how effective the low interest rate program is in increasing sales at PT Home Credit Indonesia East Bandung district for the past 1 year.The method used in this research is quantitative method. This research was conducted by means of observation at the Home Credit Indonesia East Bandung district to collect sales report data. The statistical method used by the author is using SPSS version 26 with the normality test, T-test, and independent sample t-test.The results showed that the low interest rate program was effective in increasing sales. The low interest rate program has an effect on increasing sales. The suggestion for the Home Credit company is for stores that have not participated in the low interest rate program to participate in the low interest rate program in order to increase sales for both the store and the Home Credit Indonesia company itself.